(B-5) (7-5b) -2 (b + 2) (b-6) =

(B-5) (7-5b) -2 (b + 2) (b-6) =

  • 1) (B - 5) * (7 - 5B) = 7B - 5B - 35 + 25B = - 5B + 32B - 35
    2) - 2 * (B + 2) = - 2B - 4
    3) (- 2B - 4) * (B - 6) = - 2B + 12B - 4B + 24 = - 2B + 8B + 24
    4) - 5B + 32B - 35 - 2B + 8B + 24 = - 7B + 40B - 11
    Відповідь - 7B + 40B - 11
  • (B-5) (7-5b) -2 (b + 2) (b-6) = 7b-5b ^ 2-35 + 25b-2 (b ^ 2-6b + 2b-12) = 7b-5b ^ 2-35 + 25b-2b ^ 2-12b + 4b-24 = 24b-7b ^ 2-59
    Ну а далі через дискримінант або теорему Вієта, якщо проходили вже
  • Понравилась статья? Поделиться с друзьями:
    Добавить комментарий

    92 − = 84

    ;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!: